Analisis Pengendalian Persediaan Sistem Manajemen Persediaan Bahan Baku Kemasan - Suryani, Suryani; Can, Dedi (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2018)
Inventory is one of the things that must be considered by the company. One way is to manage inventory management. The problem that occurs in the research location is the lack and excess stock for packaging raw materials. This lack of capital is due to the absence of calculations for the number of safety stock and reorder points, the cause of excess inventory is the excess in the absence of groupings of packaging raw materials to find out which products are more critical according to demand. Analysis of system improvements focuses on packaging raw materials. Based on the results of data processing obtained from 304 existing packaging raw materials, there are 15 packaging raw materials in class A. Processing is focused on class A only. Forecast calculations using SPSS software. And processing is continued by using the size-reorder point systems lot method with quantity results, reorder margin and safety stock that varies 15 raw materials according to the calculations performed.